Shortage of Radiologists in Low to Middle Income Countries in the Interpretation of CT scans in Trauma (Bangladesh Journal of Medical Science, 2022)
Abstract not availableBangladesh Journal of Medical Science Vol. 21 No. 03 July’22 Page: 489-491